Biology-Based Accelerated Learning in Communication - Nurlaelah, Nurlaelah (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The quality of human resources is an important sector in supporting the achievement of national development goals. National development requires superior quality human resources in the fields of science, technology, arts, sports, noble character, and devotion to God Almighty. Specially gifted children are a resource that can make a meaningful contribution to the progress of the nation and state. The rationale for organizing and continuing to develop educational efforts for gifted children is to provide educational services that suit the potential of gifted children. By preparing potential human resources who will be able to encourage the nation's progress. One form of education for gifted children is the acceleration program, namely the provision of educational services in accordance with the potential intelligence and special talents possessed by students, by giving them the opportunity to complete the regular program in a shorter period of time compared to their peers. her friend.